The World Bank Group and Foundations : Stories of Partnership 2014 - World Bank Group (Washington, DC, 2015)
Today, the World Bank Group works with over 80 foundations around the world. This publication brings together examples of those partnerships. The report is not comprehensive, but an attempt to capture a sense of the breadth and extent of collaboration between the World Bank Group and the philanthropic sector. It tells the story of the power of partnerships and what can be achieved by working together. We are collaborating on development priorities ranging from job creation to citizen engagement and social accountability to health, education, financial inclusion to climate change and building resilient, inclusive cities for the 21st century. This publication makes clear how these projects are bringing real change to people's lives and to our planet. In Sub-Saharan Africa, the MasterCard Foundation and the International Finance Corporation (IFC) are bringing low-cost financial services to an estimated 5.3 million people who do not have a bank account; the Adolescent Girls' Initiative, a partnership between the World Bank Group and the Nike Foundation, has trained 2,500 women in Liberia to support their transition to productive work, and helped raise employment by almost 50 percent; in India, Indonesia, and Tanzania, a project with the Bill and Melinda Gates Foundation has led to more than 4 million people deciding to stop open defecation and begin using basic sanitation facilities; and in the Philippines, the World Bank Group's Global Partnership for Social Accountability and the Open Society Foundations are supporting an initiative called Checkmyschool to give students and parents a say in how their schools are run.